2020
DOI: 10.31616/asj.2019.0065
|View full text |Cite
|
Sign up to set email alerts
|

Superior Facet Joint Violations in Single Level Minimally Invasive and Open Transforaminal Lumbar Interbody Fusion: A Comparative Study

Abstract: To compare the incidence of iatrogenic superior facet joint violation (SFV) in minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) and open TLIF (OPEN-TLIF) at a single lower lumbar fusion level and to evaluate the patient and surgical factors influencing the outcome. Overview of Literature: Iatrogenic SFV is a significant risk factor for adjacent segment disease (ASD). Blind screw placement technique in MIS-TLIF contributes to the increasing incidence of iatrogenic SFV which can be influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…During MIS TLIF, when pedicle screws are placed percutaneously, careful attention needs to be paid to avoid iatrogenic superior facet joint violation, which is a known risk factor for ASD. 23 Whereas revision for pseudarthrosis was only seen in the open cohort in our study, pseudarthrosis is also a potential long-term complication of MIS TLIF. 17,24 In our study, there were statistically significant improvements in VAS and ODI after MIS and open TLIF.…”
Section: Discussionmentioning
confidence: 58%
“…During MIS TLIF, when pedicle screws are placed percutaneously, careful attention needs to be paid to avoid iatrogenic superior facet joint violation, which is a known risk factor for ASD. 23 Whereas revision for pseudarthrosis was only seen in the open cohort in our study, pseudarthrosis is also a potential long-term complication of MIS TLIF. 17,24 In our study, there were statistically significant improvements in VAS and ODI after MIS and open TLIF.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the present study revealed that a smaller facet angle and older age were significant risk factors independent of the surgical technique. Teles et al [ 39 ] and Patel et al [ 40 ] compared the incidence of FJVs between percutaneous and open screw placement and found that facet angle was an independent risk factor for FJVs. The morphology of the facet joint varies greatly among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…27 In line with these findings, Hsiang et al 28 also report on a series of MIS TLIFs in which 5% of the cohort had an aberrant screw placement that not only presented as a new onset of leg pain but also required a surgical revision to correct the screw placement. Another recent study by Patel et al 29 looked at rates of superior facet joint violations in both MIS and open TLIF surgeries. They found that MIS had more superior facet joint violations overall.…”
Section: Increased Surgical Complicationsmentioning
confidence: 99%
“…This increased rate of superior facet violations places patients at increased risk of adjacent segment disease in the future. 29 The increased frequency of nerve root injuries and facet joint violations may be a direct result of limited visualization in MIS TLIFs, indicating that the technique itself leads to an increased number of surgical complications.…”
Section: Increased Surgical Complicationsmentioning
confidence: 99%